PENERAPAN STRATEGI KOOPERATIF TEKNIK MURDER YANG DIKOLABORASIKAN DENGAN NUMBERED HEADS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI SMK SEMEN PADANG TAHUN PELAJARAN 2013/2014 - Irawati, Lina; Haryono, Yulia; Suryani, Mulia (Pendidikan Matematika, 2014)
ABSTRACTThis research was conducted based on the phenomena indicating that the students tended to be noisy during the learning process and they got low understanding on mathematics concept. This research aimed to reveal whether the use of MURDER technique of cooperative strategy collaborated with Number Heads could improve the studentsâ understanding on mathematics concept better than that of conventional technique. This was an experimental research. The data gotten then was analyzed by using t-test assisted with software MINITAB. Based on the result of data analysis, it was found that P-value was 0.019 which was smaller than Î± = 0.05. This result indicated that the mathematics conceptual understanding of the students taught by using MURDER technique of cooperative strategy collaborated with Number Heads was better than that of students taught by using conventional technique in which the level of the reliability was 95%.Â